Community advisory boards as implementation strategies to center partner and patient voice in community health centers - Rebekka M. Lee; Kamini Mallick; James G. Daly; Vetta Sanders Thompson; Elise Hoffman; Maria Papadopoulos; Stacey Curry (Journal of Clinical and Translational Science)
Abstract